Progesterone selectively reduces IFN-γ release by human fetal specific cytotoxic T cell clones. (7th June 2011) - Lissauer, D; Long, H; Goodyear, O; Coomarasamy, A; Moss, P A H; Kilby, M D
Abstract : Progesterone (P4) has immunomodulatory effects during pregnancy, including shifting CD4 T cell clones from a Th1 toTh2 profile. Effects on CD8+ T cell (CTL) clones have not been described. Maternal CTL specific for fetal (HY) antigen are present during human pregnancy. Mechanisms of tolerance, including the action of progesterone, may regulate their action in-vivo. We studied the effect of P4 on the function of fetal-specific CTL. Maternal CTL specific for fetal antigen were cloned during human pregnancy. Clones were stimulated by antigen expressing targets in media containing natural P4 at a range of concentrations. The production of interferon-α (IFN-α) was measured by ELISA. All experiments were conducted in triplicate. Results show IFN-α release by fetal-specific T cell clones was significantly reduced (median 36% reduction, p=<0.001) following short term exposure to P4 at 20 µM (n=4). Control Epstein-Barr virus-specific CTL clones (CD8 n=5, CD4 n=4) did not demonstrate reductions in IFN-α release at 20 µM, and significant reduction in IFN-α release was only seen at 100 µM. Flow cytometric assays showed this was not due to reduced viability. Comparisons of endogenously processed antigen and antigen loaded targets revealed it was not due to antigen presentation. IFN-α release by fetal-specific CTL clones is reduced by concentrations of progesterone similar to those found in the human decidua. Work is ongoing to isolate the cellular mechanisms of this effect and determine why fetal-specific clones respond differently. Understanding the mechanism of action of progesterone on fetal-specific CTL is important as progesterone is used therapeutically and could be manipulating fetal-specific T cell responses.